Novel 1064 nm DBR lasers combining active layer removal and surface gratings. Issue 14 (2nd May 2021) - Brox, O.; Wenzel, H.; Fricke, J.; Della Casa, P.; Maaßdorf, A.; Matalla, M.; Wenzel, S.; Wicht, A.; Knigge, A.
Abstract: The fabrication and characterisation details of novel distributed Bragg reflector (DBR) diode lasers emitting around 1064 nm are presented here. The AlGaAs epitaxial layer stack used here allows the removal of the active quantum wells in passive sections where no current is injected. The DBR lasers fabricated with a two‐step epitaxial approach without an active layer in the grating sections show improved performance in terms of power, efficiency, and linewidth in comparison to its all‐active DBR counterparts.